Ground penetrating radar applied to environmental analysis post remediation gas stations - Souza, Danusa Mayara de (2017)
Underground aquifers are much less vulnerable to contamination than surface waters; however, once contamination has occurred, its recovery, depending on the type of contaminant, can take many years and even become economically unfeasible. Due to urban occupation, groundwater is exposed to several types of contaminants and among them are the hydrocarbons. The fuels derived from petroleum have a high electric resistivity and when spilled on the ground increase the resistivity of the environment. After some time, commonly, the action of bacteria over the organic compounds of fuels produce their biodegradation with the formation of acid that dissolve ions of the material of the ground, lowering the electric resistivity and transforming the environment into a good conductor of electricity. In this work it was intended to detect the signature in terms of resistivity of anomalies associated to contamination by fuels derived from hydrocarbons at the Braz de Aguiar Gas Station, a deactivated station, located in Belém/PA. The geophysical measurements were carried through with the Ground Penetrating Radar (GPR) using a 400 MHz antenna and the data were processed with the REFLEXW software. A low resistivity signature was detected even after the remediation performed in the study gas station.